(untitled) (Cardiovascular Journal, 2021)
Background: Primary percutaneous coronary intervention (pPCI) is the preferred and established mode of treatment in ST elevated myocardial infarction (STEMI). Exact data on procedural outcome in patient undergoing primary PCI in our population is not well documented. Therefore, we have carried out this study to see the prognosis, in-hospital, and 12-month survival outcome of our patients. Methods: Patients were enrolled in the observational non-randomized prospective cohort between November 2017-Mar 2020, who were presented into our emergency department with acute onset of severe chest pain or angina with ECG evidenced acute ST elevated myocardial infarction. Total 182 patient (F 14; Male 168) were enrolled in this study. Results: Out of 182 patients, female :14 (7.7%) vs. Male: 168 (92.3%). Among, these patient females were more obese (BMI: Female 27.1 ± 2.1 vs. male 25.8 ± 4.1) and developed CAD in advance age (Female 59.1 ± 13.5 vs. Male 53.7 ± 10.5). Anterior MI were 47.8% (n=87) and Inferior MI 50.5% (n=92) and Lateral MI 1.6% (n=3). At presentation 10.4% (n=19) patents were in cardiogenic shock with STEMI, 42.1%(n=8) patients with Ant MI, 57.9%(n=11) in Inf MI group. Total, 15 (8.2%) patients died; 93.3%(n=14) within 1 week of pPCI due shock and poor LV function and subsequent development of LVF with arrhythmia and 6.7%(n=1) patient died 6 months after pPCI due to other cause. Death was more in Ant Wall STEMI than Inferior wall STEMI, though Cardiogenic shock at presentation were more in Inf MI STEMI than Ant wall STEMI. Conclusion: We may conclude from our observational study on STEMI PCI that the territory wise involvement of myocardium, baseline serum Troponin-I level, infarcted vessel, time to presentation, duration of anginal chest pain and door to balloon time may be the key determinant of better in hospital outcome. Cardiovasc. j. 2021; 13(2): 154-163